2018
DOI: 10.1167/18.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Visual crowding is unaffected by adaptation-induced spatial compression

Abstract: It has recently been shown that adapting to a densely textured stimulus alters the perception of visual space, such that the distance between two points subsequently presented in the adapted region appears reduced (Hisakata, Nishida, & Johnston, 2016). We asked whether this form of adaptation-induced spatial compression alters visual crowding. To address this question, we first adapted observers to a dynamic dot texture presented within an annular region surrounding the test location. Following adaptation, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In contrast, in other locations, the target–flanker spacing may be perceived as larger, resulting in weaker crowding and making it easier for the observer to identify a crowded object. This prediction aligns with previous work showing that crowding critically depends on the perceived, rather than physical, separation between the target and flankers ( Dakin, Greenwood, Carlson, & Bex, 2011 ; Maus, Fischer, & Whitney, 2011 ; although see Chambers, Johnston, & Roach, 2018 for a counter-example). However, these studies manipulated perceived separation by introducing changes to the stimulus directly (i.e., by adding motion).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, in other locations, the target–flanker spacing may be perceived as larger, resulting in weaker crowding and making it easier for the observer to identify a crowded object. This prediction aligns with previous work showing that crowding critically depends on the perceived, rather than physical, separation between the target and flankers ( Dakin, Greenwood, Carlson, & Bex, 2011 ; Maus, Fischer, & Whitney, 2011 ; although see Chambers, Johnston, & Roach, 2018 for a counter-example). However, these studies manipulated perceived separation by introducing changes to the stimulus directly (i.e., by adding motion).…”
Section: Introductionsupporting
confidence: 91%
“…We show similar effects in the absence of such an illusory shift, showing that crowding can be influenced by heterogeneity in perceived spacing around the visual field. However, other work has shown that the strength of crowding does not always follow illusory displacements in perceived position (e.g., Chambers et al, 2018 ) and can also depend on perceptual grouping and flanker arrangement ( Herzog, Sayim, Chicherov, & Manassi, 2015 ; Manassi, Sayim, & Herzog, 2013 ). Critically, these results likely reflect that crowding occurs at multiple stages of visual processing and future studies could extend our paradigm to examine how these factors intersect with spatial variability in visual space perception.…”
Section: Discussionmentioning
confidence: 95%
“…The forgoing effects of adaptation and learning on accuracy were not associated with changes in precision. Consistent with this, Chambers et al (2018) showed that adaptation to a textured annulus (a stimulus similar to those producing the forgoing effects of adaptation and learning) produces perceived compression in the region surrounded by the annulus but no change in crowding within that region. More recently, however, changes in precision have been observed that may reflect similar mechanisms as do the forgoing adaptation and learning effects.…”
Section: Supporting the Indirect Viewmentioning
confidence: 55%
“…However, in this study, eccentricity was confounded with distance between adapted and test locations. Another study found robust compression effects in the absence of any spatial overlap between adaptor and test ( Chambers, Johnston, & Roach, 2018 ). However, in this study, the adaptor was an annulus comprising dots whose luminance was sinusoidally modulated over time, and the test was an array of dipoles (pairs of dots) placed inside the area surrounded by the annular adaptor.…”
Section: Discussionmentioning
confidence: 99%